Uma abordagem investigativa com o uso do método POE no estudo da interação entre as moléculas e a luz - Mesquita, Thaís Martins Oliveira (2022)
In this work, we discuss an educational product developed that uses an active methodology, the POE method (predict, observe and explain) linked to a computational experiment of the PHET simulations portal. It was verified through a case study, the suitability of this method to this tool in the context of remote teaching in the teaching of Modern and Contemporary Physics. The product was developed based on the observation of difficulties reported by students and teachers in relation to the complexity of the content of Modern and Contemporary Physics (FMC), considers issues such as motivation and concentration in the learning process. It was sought to meet pre-established pedagogical objectives, such as stimulating and providing more meaningful learning, through an investigative approach. And also facilitating an effective conceptual change in students through simulations that provide an opportunity to visualize complex concepts of the FMC, notably the interaction between light radiation and matter. In the taught class, the three steps of the method were applied in order to build a sequence of increasing complexity, with topics related to the interaction of light photons of different characteristics of light and matter. Content fixation was evaluated through a form with steps to be completed before, during and after the use of the virtual experiment. It was considered feasibility to apply the POE method, in this context of FMC teaching, as well as the achievement of objectives regarding the development of critical thinking, the occurrence of conceptual changes and the appropriation of scientific language by the participants.